LAMANYA PERAWATAN PASIEN SKIZOFRENIA RAWAT JALAN DENGAN TINGKAT STRES KELUARGA - Jek Amidos Pardede; Eva Kartika Hasibuan (Universitas Murni Teguh, 2020)
Schizophrenia is one form of chronic mental disorder, which causes serious persistent brain disease that results in psychotic behavior, concrete thinking, and difficulty in obtaining information. Prolonged treatment in schizophrenia patients will generally cause stress to families related to the high burden they bear.The purpose of this research is to know the relationship between the duration of treatment schizophrenia patients with the level of family stress.The design of this research is a descriptive correlation with the Cross-Sectional approach. The population of this study amounted to 181 people and samples of this study as many as 64 respondents.Sampling techniques with accidental sampling. The collection of data using questionnaires with test Chi-Square p = < 0.005. The results of this study showed that there is a connection between the duration of treatment schizophrenia patients with a level of family stress in the hospital psychiatric clinic Prof.Dr. Muhammad Ildrem Medan. From 64 respondents there were 43 respondents experiencing moderate stress (67.2%), 11 respondents experiencing severe stress (17.2%), and 10 respondents experiencing mild stress (15.6%).The results of this study indicate there is a significant relationship between the length of treatment with the level of family stress with P=0.035 or P=0.05.This research is expected that families are able to anticipate their stressements by giving support to schizophrenia patients. Abstrak Skizofrenia merupakan salah satu bentuk gangguan jiwa kronik, yang menyebabkan penyakit otak persisten serius yang mengakibatkan prilaku psikotik, pemikiran konkret, dan kesulitan dalam memperoleh informasi. Perawatan yang lama pada pasien skizofrenia umumnya akan menimbulkan stress kepada keluarga terkait tingginya beban yang mereka tanggung. Tujuan penelitian ini untuk mengetahui hubungan antara lamanya perawatan pasien skizofrenia rawat jalan dengan tingkat stress keluarga. Desain penelitian ini adalah deskriptif korelasi dengan pendekatan Cross-Sectional. Populasi penelitian ini berjumlah 181 orang dan sampel penelitian ini sebanyak 64 responden. Tehnik pengambilan sampel dengan accidental sampling. Pengumpulan data mengunakan kuesioner dengan menggunakan uji Chi-Square p= <0,05. Hasil penelitian ini menunjukan adanya hubungan antara lamanya perawatan pasien skizofrenia rawat jalan dengan tingkat stress keluarga di Poliklinik Rumah Sakit Jiwa Prof. Dr. M. Ildrem Medan. Dari 64 responden terdapat 43 responden mengalami stress sedang (67,2%), 11 responden mengalami stress berat (17,2%), dan 10 responden mengalami stress ringan (15,6%). Hasil penelitian ini menunjukan ada hubungan signifikan antara lamanya perawatan dengan tingkat stress keluarga dengan p=0,035 atau p=0,05. Penelitian ini diharapkan keluarga mampu mengantisipasi stresnya dengan memberi dukungan pada pasien skizofrenia.